Rules of origin and the European Union's preferential trade agreements, with special reference to the EU-ACP Economic Partnership Agreements - Peter Gibbon (Danish Institute for International Studies (DIIS), 2008)
Economic opinion is in the process of re-interpreting low levels of uptake of non-reciprocal pre-ferential trade agreements (PTAs) partly in terms of administrative barriers to preference utiliza-tion. Primary amongst these barriers are Rules of Origin. This paper reviews the literature on Rules of Origin as administrative barriers to the utilization of preferences accorded to African, Caribbean and Pacific (ACP) countries under the Coutonou Agreement, before going on to ex-amine current revisions of EU PTA Rules of Origin. These are embodied in a new (so-called 'Cotonou+') set of rules for the interim EU-ACP Economic Partnership Agreements (EPAs) and a second proposed set of rules for the EU's Generalised System of Preference (GSP) arrange-ments, including Everything But Arms. The Cotonou+ rules include some important concessions by the EU, especially for those ACP countries that do not have Least Developed Country (LDC) status, but are supposed to be re-negotiated within a fixed period in line the new EU GSP rules. However, the new GSP rules as revealed in the EU Draft Regulation of 2007 contain no real concessions for non-LDCs, and they introduce potentially trade-restrictive administrative require-ments. These rules are currently (July 2008) under reconsideration by the EU, but it is clear that this exercise does not cover these elements. For this reason, harmonisation of the Cotonou+ and new GSP rules may be a source a serious discord in the negotiation of full EPAs, a process which is supposed to occur during 2008.
Keywords: 330; Internationale Wirtschaftsbeziehungen; Handelsabkommen; Außenhandelspräferenz; Zollpräferenz; Ursprungslandprinzip; Fischprodukt; Textilien; EU-Staaten; AKP-Staaten